ECG Data Analysis Using the Convolution of Mealy and Moore Automata - Martusevičienė, A.; Navickas, Z.; Vainoras, A. (Elektronika ir Elektrotechnika, 2010)
Clinical decision support systems are interactive computer programs. Most advanced of these systems are based on mathematical models. In this paper model of convolution of Mealy and Moore automata for real time ECG data analysis is introduced. The proposed model helps to effectively organize the feedback between current patient functional state and applied influence. Mathematical formalization of the system is also provided. Ill. 4, bibl. 6 (in English; abstracts in English, Russian and Lithuanian).